2009
DOI: 10.1209/0295-5075/88/67006
|View full text |Cite
|
Sign up to set email alerts
|

Charge carrier untrapping by temperature effects in conjugated polymers

Abstract: The temperature influence on charge carrier dynamics is fundamental for the description of the performance of organic diodes and transistors. In this work we treat the temperature on charge transport of both intrachain and interchain process, considering situations where the charge carriers are initially bound in some aspect. We obtain in both cases that the temperature increase can raise the carriers mobility by the same mechanism. The reasons for mobility increase are charge carrier delocalization as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…When temperature effects are considered, we observed that on a single chain, a polaron-exciton suffers spontaneous dissociation forming a free polaron. These results are in good agreements with experimental data [103] and previous theoretical simulations [49] performed for weakly coupled chains bearing a polaron-exciton. We concluded that temperature effects are important in the processes of recombination, particularly in the single-molecule polaron-exciton dissociation process, which does not occur without the influence of temperature.…”
Section: Charge Carriers and Excited Statessupporting
confidence: 91%
“…When temperature effects are considered, we observed that on a single chain, a polaron-exciton suffers spontaneous dissociation forming a free polaron. These results are in good agreements with experimental data [103] and previous theoretical simulations [49] performed for weakly coupled chains bearing a polaron-exciton. We concluded that temperature effects are important in the processes of recombination, particularly in the single-molecule polaron-exciton dissociation process, which does not occur without the influence of temperature.…”
Section: Charge Carriers and Excited Statessupporting
confidence: 91%
“…We use γ = 0.06 fs –1 . This value was chosen by taking into account the typical frequency of C–C bond oscillation on π-conjugated systems (∼1500 cm –1 ). ,,, …”
Section: Methodsmentioning
confidence: 99%
“…It is expected that at low temperatures only the normal modes with low frequencies will be excited, and a classical treatment for the lattice should provide a poor description of the intrachain problem. Many studies that use the same method consider intermolecular transport, which is governed by phonons with much lower frequencies (100–200 cm –1 ). , On the other hand, intrachain phenomena have also been treated with similar approaches, providing excellent qualitative results. ,, This can be seen as the consequence of the strong electron–phonon coupling inherent to conjugated polymers. In fact, the assumption that atoms are frozen in their equilibrium positions for carbon-based nanostructures can lead to inaccurate results .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the model system used here is a pristine lattice. Therefore, this critical limit for the polaron diffusion in real systems www.nature.com/scientificreports www.nature.com/scientificreports/ should be, in fact, substantially smaller due to, for instance, lattice defects and charge recombination that can reduce the mean free path of charge carriers in organic semiconductors 39,40 .…”
mentioning
confidence: 99%